Pemberdayaan Ibu Rumah Tangga dalam Implementasi Teknologi Pengolahan Sumber Karbohidrat Nonberas dan Penganekaragaman Pangan Nonterigu untuk Mendukung Ketahanan Pangan - Rudiati Evi Masithoh; Heni Kusumawati (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2016)
Community may be involved in food security program by utilizing local based food materials in their surrounding areas. Potency of local food in Indonesia can be used as an alternative for the staple food. Te huge number of housewives in Yogyakarta can support the family economy or reduce the household budget through the use of local food sources. Tis community service activities aiemed at providing an understanding of processing technology of non-rice and non wheat food resources to be utilized to achieve food security and improve household economy. Outcomes of this activity are non-rice food products as carbohydrates source and non - grain food diversifcation, an improved understanding of food processing technology, as well as increased understanding of marketing and entrepreneurship.